Máxima fase estável de lactato é ergômetro- dependente em modelo experimental utilizando ratos - Manchado, Fúlvia De Barros [UNESP]; Gobatto, Claudio Alexandre [UNESP]; Contarteze, Ricardo Vinícius Ledesma [UNESP]; Papoti, Marcelo [UNESP]; De Mello, Maria Alice Rostom [UNESP] (My University, 2006)
The maximal lactate steady state (MLSS) is considered the gold standard method for determination of aerobic/anaerobic metabolic transition during continuous exercise, but the blood lactate response at this intensity is ergometer-dependent in human beings. An important tool for exercise physiology and correlated fields is the use of animal models. However, investigation on evaluation protocols in rats is scarce. The aim of the present study was to verify if the MLSS is ergometer-dependent for the evaluation of the aerobic conditioning of rats. Therefore, 40 adult male Wistar rats were evaluated in two different exercise types: swimming and treadmill running. In both, the MLSS was obtained with 4 continuous 25 minutes tests, at different intensities, performed at 48 hours intervals. In all tests, blood samples were collected from a cut at the tail tip every 5 minutes for blood lactate analysis. The swimming tests occurred in a deep cylindrical tank, with water temperature at 31 ± 1°C. The loads used in the tests were 4.5; 5.0; 5.5 and 6.0% of the body weight tied to the animal's back. For MLSS determination in running exercise, there was selection of running rats and velocities used in the tests were 15, 20, 25, 30 m.min-1. The MLSS was interpreted as an increase not exceeding 1.0 mM of blood lactate, from the 10th to the 25 th minute of exercise. The MLSS in swimming exercise occurred at 5.0% of body weight (bw), with blood lactate at 5.20 ± 0.22 mM. The running rats presented MLSS at the 20 m.min-1 velocity, with blood lactate of 3.87 ± 0.33 mM. The results indicated that the MLSS is ergometer-dependent in experimental models using animals, as it is in human beings.
The maximal lactate steady state is ergometer-dependent in experimental model using rats
Keywords: Blood lactate; Swimming; Treadmill running; Wistar rats